Exploring the Mediating Role of Online Social Capital in the Association Between Sharing Memes Using Four Humor Styles and Subjective Well-Being - Yueming Luo; Yu-Leung Ng (Social Media + Society)
Sharing memes has emerged as a prevalent form of social grooming behavior on digital platforms, yet research has largely focused on the content of internet memes rather than the behavior of sharing them. This study explores whether sharing memes with different humor styles (affiliative, self-enhancing, aggressive, and self-defeating humor styles) relates to subjective well-being through the mediating roles of online bonding and bridging social capital. Using survey data from a representative sample of 1000 participants in the United States, the findings showed that affiliative and aggressive meme-sharing were positively associated with psychological well-being and positive feelings via enhanced online bonding social capital. The findings could contribute to a deeper understanding of social and psychological implications of engaging with memes in online communication.